Pengaruh Modal Manusia, Modal Fisik, Dan Iklim Pembelajaran Terhadap Capaian Pembelajaran Kurikulum Merdeka Di Sdn 1 Boyolangu - Diana Setianingsih; M. Abdul Roziq Asrori; Kadeni Kadeni (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2023)
This study aims to (1) Analyze the influence of human capital on the learning outcomes of the independent curriculum at SDN 1 Boyolangu. (2) Analyzing the effect of physical capital on the learning outcomes of the independent curriculum at SDN 1 Boyolangu. (3) Analyzing the effect of the learning climate on learning achievement of the independent curriculum at SDN 1 Boyolangu (4) Analyzing the effect of human capital, physical capital, and learning climate simultaneously on learning achievement of the independent curriculum at SDN 1 Boyolangu. This type of research is quantitative research. The total sample in this study was 105 students. Determination of the sample in this study using saturated sample technique. The independent variable (X) in this study is teacher quality, physical capital, and learning climate. The dependent variable (Y) in the research is the learning achievement of the Independent Learning Curriculum. The data collection technique uses a questionnaire. The data analysis technique used the t regression test and the F test. The results showed that human capital (X1) did not significantly influence learning achievement in the independent learning curriculum at SDN 1 Boyolangu. Physical capital (X2) does not significantly influence the learning outcomes of the independent learning curriculum at SDN 1 Boyolangu. The learning climate (X3) has a significant effect on the learning outcomes of the independent learning curriculum at SDN 1 Boyolangu. All independent variables (human capital, physical capital and learning climate) together have a significant effect on the learning outcomes of the independent learning curriculum at SDN 1 Boyolangu.